Technology and Poverty Reduction in Asia and the Pacific (OECD Publishing, 2002)
Poverty reduction remains a major development challenge in much of Asia and the Pacific. Historically, technology has played a central role in raising living standards across the region, including those of the poor. The Green Revolution and various innovations of modern medicine and public health have been instrumental in improving nutrition, health, and livelihoods of millions of poor people. Yet, the pace of improvement from these sources appears to have slowed, and new technological impetus — as well as improved policies and institutions — are needed to address the persistent poverty problem in some regions and among some social groups. Agricultural and medical biotechnology hold tremendous promise but also bring with them new risks and concerns that need to be addressed before their full potential can be realised. New information technologies are only beginning to diffuse widely in developing Asia and the Pacific, but ultimately these too can have profound impacts on the lives of the poor, empowering them with access to information that once was the preserve of the privileged few.
Keywords: Asien; Pazifischer Raum; Irland; Portugal; Thailand; China; Aufsatzsammlung; Konferenzschrift; Technologie; Bekämpfung; Armut; Asiatisch-Pazifischer Raum